Running speed rating conditions and factors: theoretical grounds and practical tests - Katenkov, A. N.; Anisimova, E. A.; Novikov, E. M. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to increase the sprint running speed based on the factors that determine the effectiveness of training and competitive activities.